Growth of GaSb / GalnAsSb / GaSb heterostructures using the liquid phase epitaxy technique (Revista de Investigaciones Universidad del Quindío, 2009)
In this paper we show some preliminary results of the liquid phase epitaxy growth process for the heterostructures GaSb/GaInAsSb/GaSb. We describe the fabrication process of the heterostructures and also we present the analysis of its X-Ray Diffraction patterns (XRD) and Photoluminescence (PL) characterization. These results evidenced the epitaxial growth of the heterostructures.
Keywords: Semiconductors; heteroestructure; LPE; XRD; PL